On the natural Fiber (Maize) Composite material. Issue 1 (21st October 2015) - Ilie, Ruxandra; Chiroiu, Veturia
Abstract: This work is focused on the compressive behavior in the elastic region of a composite material made out of stalk‐based maize fiber and unsaturated polyester resin polymer as matrix with methyl ethyl ketone peroxide as a catalyst and Cobalt Octoate as a promoter [1]. Deformation and fracture behavior are investigated by using Extended Finite Element Method (XFEM). XFEM enables the accurate approximation of solutions with jumps, discontinuities or general high gradients across interfaces between the fibers and the matrix [2], [3]. (© 2015 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)